Late massive radial artery pseudoaneurysm following cardiac catheterization: A case report - Sharma, Radhika (Int J Surg Case Rep, 2021)
INTRODUCTION: Transradial artery approach for cardiac catheterization was first introduced in the late 1980s and has now become the approach of choice due to its anatomical advantage, reduction in complications, and overall improved patient experience. CASE PRESENTATION: We present a case of a 77 year-old female who presented with an extremely rare and late complication of radial artery pseudoaneurysm after transradial coronary intervention. The patient presented at a post-procedural follow-up with severe pain at the radial access site and was found to have a partially thrombosed pseudoaneurysm. Given the anatomical variance of the pseudoaneurysm, the patient underwent successful open surgical repair. CLINICAL DISCUSSION: Although radial artery access is a relatively safe approach in comparison to the transfemoral approach, the risk of adverse events still exists. Among the complications of the transradial approach, pseudoaneurysms are relatively rare, occurring in less than 0.1% of cases. Regardless, early identification of this complication is essential to timely intervention. CONCLUSION: Our case highlights the importance of post procedural monitoring and early identification and diagnosis of the complication to facilitate appropriate therapy.